2017
DOI: 10.1088/1361-665x/26/2/025033
|View full text |Cite
|
Sign up to set email alerts
|

Smart washer—a piezoceramic-based transducer to monitor looseness of bolted connection

Abstract: The safety of a bolted connection, as one of the most common ways of making two or more parts/components work together in engineering structures, is very important in order to ensure the health of the whole structure. However, bolt loosening or pre-load degradation may induce the failure of the bolt connection, threatening the normal operation of the system's structure. As a result, it would be beneficial if the health condition of the bolt connection could be monitored in real time. In this paper, a 'smart wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 38 publications
4
64
0
Order By: Relevance
“…Hisakado et al [105] found that the mean friction coefficient increased with the mean AE event counting under the various lubricated conditions. Extensive efforts have been dedicated to studying the monitoring of connection components [106][107][108][109][110][111]. However, there are few studies that focus on the wear process of pin connections.…”
Section: Introductionmentioning
confidence: 99%
“…Hisakado et al [105] found that the mean friction coefficient increased with the mean AE event counting under the various lubricated conditions. Extensive efforts have been dedicated to studying the monitoring of connection components [106][107][108][109][110][111]. However, there are few studies that focus on the wear process of pin connections.…”
Section: Introductionmentioning
confidence: 99%
“…The time-reversal method has better antinoise performance, and the properties of temporal compression in the time domain and spatial focusing in the spatial domain were also better [21]. According to Huo et al's research, PZT sensors are very suitable as a time-reversal mirror in the time-reversal process [12]. Therefore, PZT sensors are invoked as actuators and sensors for bolt looseness monitoring.…”
Section: Principle Of the Proposed Methodsmentioning
confidence: 99%
“…Figure 3 illustrates the wavelet decomposition at level 4. The specimens in each signal set can be represented by X ij , as follows [12]:…”
Section: Principle Of the Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations